Effect of remote ischaemic conditioning on coagulation function as measured by whole blood impedance aggregometry and rotational thromboelastometry in off-pump coronary artery bypass surgery: A randomised controlled trial. Issue 187 (March 2020) - Kim, Tae Kyong; Nam, Karam; Cho, Youn Joung; Choi, Seungeun; Row, Hyung Sang; Jeon, Yunseok
Abstract: Introduction: Remote ischaemic conditioning (RIC) has been shown to prevent platelet activation during ablation for atrial fibrillation. RIC has also been associated with more postoperative transfusion in the off-pump coronary artery bypass graft surgery (OPCAB) patients. We evaluated the effects of RIC on coagulation function in OPCAB patients. Methods: A total of 58 patients undergoing OPCAB were randomised to the RIC or control group. In the RIC group, four cycles of 5 min of ischaemia and 5 min of reperfusion were applied twice to the upper arm after the induction of anaesthesia (preconditioning), and after the completion of coronary anastomoses (postconditioning). Whole blood impedance aggregometry (Multiplate®) and rotational thromboelastometry (ROTEM®) were performed before the induction of anaesthesia, at the end of surgery, and at postoperative day 1. Results: The trend towards a decrease in adenosine diphosphate-induced whole blood aggregation at the end of surgery was greater in the RIC group than in the control group, but this effect was not statistically significant (−10.4 [18.1] vs. −5.7 [24.8] U, P = 0.424). In ROTEM® analysis, the EXTEM area under the velocity curve was lower in the RIC group than in the control group at the end of surgery (3567 [1399–5794] vs. 5693 [4718–6179] mm∗100, respectively; P = 0.030). A tendency of larger perioperative blood loss was identified in the RIC group. Conclusions: Although some parameters indicated a tendency for hypocoagulation in the RIC group at the end of surgery, most effects were not statistically significant. RIC does not significantly affect perioperative platelet aggregability and coagulation in patients undergoing OPCAB. Highlights: RIC has been associated with increased red blood cell transfusion in off-pump coronary artery bypass graft surgery. A total of 58 patients undergoing off-pump coronary artery bypass graft surgery were randomized to the RIC or control group. The decrease in ADP-induced whole-blood aggregation at the end of surgery was not statistically different between the RIC and control groups. RIC does not significantly affect perioperative platelet aggregability and coagulation in off-pump coronary artery bypass graft surgery.